Investigation of the Concrete Shrinkage using an Embedded Long Period Fiber Gratings (LPFGs) - Wong, Su Khen (2015)
Measurement of concrete shrinkage is an important parameter for civil industry to ensure that the structure of concrete is capable to support the building requirements. In this project, some research works carried out to investigate of the concrete shrinkage using an embedded Long Period Fiber Gratings (LPFGs). A LPFGs will be used in this project in order to provide an alternative way to measure concrete shrinkage as comparing with the conventional way to measure concrete shrinkage which using strain gauge. By using LPFGs to measure concrete shrinkage might be a better way as compared with conventional way. The main advantage of this method is LPFG embedded inside the concrete which can detect the shrinkage changes internally. Apart from that, LPFG can measure the concrete shrinkage start from liquid state as nowadays there is no technology is able to measure the concrete shrinkage in liquid state. In this study, the main focus is how to measure the concrete shrinkage by using LPFG as a sensor.